The Translational Physiologist in Strengthening Research to Enhance Quality of Life (Nigerian Journal of Physiological Sciences, 2024)
Thematic Lecture presented to the Physiological Society of Nigeria at its 41st Annual Scientific Meeting held at the Rivers State University, Port-Harcourt, Rivers State from February 11 - 17, 2024